PENGARUH KOMPETENSI KARYAWAN, LINGKUNGAN KERJA DAN MOTIVASI KERJA TERHADAP KINERJA KARYAWAN DINAS PENANAMAN MODAL DAN PERIZINAN TERPADU SATU PINTU KABUPATEN DHARMASRAYA - Mayroza Wiska; Eka Ermawati; Metri Ronaldi (Universitas Sarjanawiyata Tamansiswa, 2022)
The One Stop Integrated Licensing Investment Office (DPMPTSP) Dharmasraya is one of the agencies whose functions are to prepare investment plans, review the development of the investment climate, carry out investment promotions, and provide investment licensing services. This study wants to see how far the influence of employee competence, work environment and work motivation on employee performance. This study was conducted to determine and analyze what kind of influence is caused by the influence of employee competence, work environment and work motivation on employee performance. The purpose of this study was to determine and analyze